Altered Reward Circuit Function Moderates the Relationship between Childhood Maltreatment and Depression Severity in Adolescents - Li, Weicheng; Hu, Zhibo; Wang, Chengyu; Lan, Xiaofeng; Zhang, Ming; Zhang, Fan; You, Zerui; Ye, Yanxiang; Liu, Haiyan; Luo, Zhanjie; Zeng, Yexian; Chen, Yiying; et al. (Depression and Anxiety, 2023)
Background. The role of childhood maltreatment (CM) is believed to be crucial in the aberrant function of reward circuit in adolescent-onset major depressive disorder (AO-MDD). Nevertheless, the impact of abnormalities in the GP-based reward circuit on the association between CM and the severity of AO-MDD remains largely unknown. Methods. The GP-based resting-state functional connectivity (RSFC) was analyzed in a sample of 75 patients with AO-MDD and 80 healthy controls in order to identify potential abnormalities in the GP-based reward circuit in AO-MDD patients. Furthermore, we investigated the possible associations between aberrant GP-based reward circuit functioning, CM and its subtypes (namely, childhood abuse and childhood neglect), and the severity of AO-MDD. Results. Compared to the healthy control group, patients with AO-MDD demonstrated a reduction in RSFC between the left posterior GP and the right dorsomedial prefrontal cortex (DMPFC). Our moderation analysis revealed that the abnormal RSFC between the posterior GP and DMPFC had a moderating effect on the relationship between CM and the severity of AO-MDD. Furthermore, upon further interaction decomposition, we observed a positive correlation between CM and AO-MDD severity exclusively in patients with AO-MDD who exhibited lower RSFC between the posterior GP and DMPFC. For AO-MDD patients with higher RSFC between posterior GP and DMPFC, the relationship between CM and AO-MDD severity was not discernible. Conclusions. Our findings underscore the crucial role of anomalies in the reward circuit in AO-MDD and furnish novel leads for probing the relationship among CM, malfunctioning of the reward circuit, and AO-MDD.